Hard carbon material prepared based on highland barley straw as well as preparation method and application of hard carbon material
By pre-oxidizing, phosphoric acid pretreatment, low-temperature activation and high-temperature carbonization of barley straw, hard carbon materials with excellent sodium storage performance were prepared, which solved the problem of orderly high-temperature carbonization in the prior art, and achieved efficient and environmentally friendly preparation of sodium ion battery negative electrode materials.
Patent Information
- Application Number
- CN202411759739.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-11
AI Technical Summary
When using barley straw to prepare hard carbon anode materials for sodium ion batteries, the lignin and cellulose in barley straw are easily ordered during direct high-temperature carbonization, which reduces the sodium storage performance of hard carbon.
By preoxidizing, phosphoric acid pretreatment, low-temperature activation and high-temperature carbonization of the barley straw powder, hard carbon materials with short-range ordered graphite microcrystals and rich closed-pore structure were prepared.
This method effectively inhibits the orderly growth of the carbon layer and improves the sodium storage performance of hard carbon materials, including improving the first-time Coulomb efficiency, circulation performance and rate performance, while achieving high-value utilization of raw materials, which has cost advantages and environmental protection characteristics.
Smart Images

Figure CN119591082A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of negative electrode materials, and in particular to a hard carbon material prepared based on highland barley straw, and a preparation method and application thereof. Background Art
[0002] With the continuous increase in global energy demand and the increasingly serious environmental pollution problem, the development of efficient and environmentally friendly energy storage devices has become an important research direction in today's society. Sodium-ion batteries, as a low-cost, abundant resource and environmentally friendly energy storage technology, have received widespread attention. Compared with lithium-ion batteries, sodium ions are abundant and inexpensive, especially in the fields of large-scale energy storage and electric vehicles, and have potential application prospects. Hard carbon is considered to be an ideal choice for sodium-ion battery negative electrode materials due to its high specific capacity, low working potential and long cycle life. According to the source of the precursor, hard carbon can be divided into resin-based, asphalt-based and biomass-based. Among them, biomass precursors have the advantages of abundant reserves, green sustainability, diverse structures, and easy regulation of physical and chemical properties. Most biomass has an ideal molecular structure, which is conducive to the diffusion of electrolytes and the transmission of sodium ions. Therefore, the development of biomass-based hard carbon materials has received widespread attention.
[0003] Highland barley is the main crop straw resource in the Qinghai-Tibet Plateau. As one of the by-products of highland barley, highland barley straw has a rich carbon content, which provides a rich source of raw materials for the preparation of hard carbon negative electrode materials, and helps to reduce the cost of sodium ion batteries. Therefore, the use of highland barley straw to prepare hard carbon negative electrode materials for sodium ion batteries can promote their high-value utilization and has important application value. When highland barley straw is used to prepare hard carbon negative electrode materials for sodium ion batteries, the lignin and cellulose in the highland barley straw are very likely to tend to long-range order during the direct high-temperature carbonization process, reducing the sodium storage performance of the hard carbon. Summary of the invention
[0004] The main purpose of the present application is to provide a hard carbon material based on highland barley straw and its preparation method and application, aiming to solve the problem that the existing highland barley straw preparation method reduces the sodium storage performance of hard carbon.
[0005] To achieve the above-mentioned purpose, the present application provides a method for preparing a hard carbon material based on highland barley straw, comprising: preparing highland barley straw powder; pre-oxidizing the highland barley straw powder to obtain pre-oxidized highland barley straw powder, wherein the pre-oxidation temperature is 150-300°C and the insulation time is 1-10h; immersing the pre-oxidized highland barley straw powder in a phosphoric acid solution to prepare a phosphoric acid-pretreated highland barley straw powder; activating and carbonizing the phosphoric acid-pretreated highland barley straw powder in sequence to obtain a hard carbon material based on highland barley straw; wherein, during the activation process, the activation temperature is 350-650°C and the activation time is 1-10h; during the carbonization process, the carbonization temperature is 1000-1600°C and the carbonization time is 1-10h.
[0006] Optionally, the mass ratio of the pre-oxidized highland barley straw powder to the phosphoric acid solution is 1:0.1-8, and the immersion time is 1-10 hours.
[0007] Optionally, the highland barley straw powder pretreated with phosphoric acid is obtained by the following method: filtering and drying the phosphoric acid solution of the highland barley straw powder obtained by impregnation; wherein the drying temperature is 80-120° C. and the drying time is 6-16 h.
[0008] Optionally, the heating rates of the pre-oxidation process, the activation process and the carbonization process are all 1-10° C. / min.
[0009] Optionally, the highland barley straw powder is obtained by the following method: peeling, crushing, washing, acid-treating, filtering and drying highland barley straw in sequence.
[0010] Optionally, the solution used for the acid treatment is a hydrochloric acid solution, a sulfuric acid solution, a nitric acid solution or a hydrofluoric acid solution.
[0011] To achieve the above objectives, the present application also provides a method for preparing a hard carbon material based on highland barley straw, which is obtained by using the above method for preparing a hard carbon material based on highland barley straw.
[0012] To achieve the above objectives, the present application also provides an application of the above-mentioned hard carbon material prepared based on highland barley straw in the negative electrode of a sodium ion battery.
[0013] Compared with the prior art, the present invention has the following beneficial effects: The method for preparing hard carbon material based on highland barley straw of the present invention comprises the following steps: acid washing highland barley straw to eliminate the adverse effects of inorganic impurities in the raw material on the sodium storage performance of the negative electrode material; then pre-oxidation is used to introduce oxygen-containing groups, and low-temperature activation with phosphoric acid is used to construct a developed microporous structure; high-temperature carbonization is then performed to shrink the pores into closed pores, and at the same time, a cross-linking reaction between phosphoric acid and oxygen-containing groups is used to inhibit the orderly growth of the carbon layer; the obtained hard carbon material has short-range ordered graphite-like microcrystals and abundant closed-pore structures, and the short-range ordered graphite-like microcrystals can promote the rapid and high-density deintercalation of sodium ions, and the closed-pore The structure increases the storage sites and transmission space of sodium ions, thereby ensuring that it has excellent sodium storage performance as a negative electrode material; the closed-pore structure can provide more sodium storage sites, accelerate the diffusion of sodium ions in the hard carbon negative electrode material, and shorten the diffusion path of sodium ions, thereby improving its first coulombic efficiency, cycle performance and rate performance; the raw material is highland barley straw agricultural waste, which has a wide source and low price and has obvious cost advantages; and production with highland barley straw agricultural waste as raw material can save resources, reduce environmental pollution, and realize the high value of agricultural waste, which is in line with the concept of green and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a SEM image of the hard carbon material prepared in Example 1 of the present application; Figure 2 This is the XRD pattern of the hard carbon material prepared in Example 1 of the present application; Figure 3 The first cycle charge and discharge curve of the hard carbon material prepared in Example 1 of the present application as a negative electrode material for a sodium ion battery at a current density of 0.02 A / g; Figure 4 The charge and discharge cycle diagram of the hard carbon material prepared in Example 1 of the present application as a negative electrode material for a sodium ion battery at a current density of 0.1 A / g; Figure 5 This is a rate diagram of the hard carbon material prepared in Example 1 of the present application as a negative electrode material for a sodium ion battery at different current densities of 0.02-2 A / g.
[0015] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in this application will be clearly and completely described below in conjunction with the drawings in this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0017] The first embodiment of the present invention provides a method for preparing a hard carbon material based on highland barley straw, which specifically comprises the following steps: Step S1, peeling, crushing, washing, acid-treating, filtering and drying highland barley straw in sequence to obtain low-ash highland barley straw powder; The solution used for the acid treatment is a hydrochloric acid solution, a sulfuric acid solution, a nitric acid solution or a hydrofluoric acid solution. The crushed highland barley straw is subjected to an acid treatment to obtain a low-ash highland barley straw powder, which can eliminate the adverse effects of inorganic impurities in the raw materials on the sodium storage performance of the negative electrode material. Highland barley straw is used as the raw material. Since highland barley grows in high-altitude alkaline land, the pore structure is relatively large, which is conducive to mass transfer.
[0018] Step S2, pre-oxidizing the highland barley straw powder to obtain pre-oxidized highland barley straw powder, wherein the pre-oxidation heating rate is 1-10° C. / min, the temperature is 150-300° C., and the insulation time is 1-10 h; In this embodiment, oxygen-containing groups can be introduced by pre-oxidizing the highland barley straw powder.
[0019] Step S3, immersing the pre-oxidized highland barley straw powder in a phosphoric acid solution for 1-10 hours at a mass ratio of 1:0.1-8, and preparing phosphoric acid pretreated highland barley straw powder; Specifically, the pre-oxidized highland barley straw powder is immersed in a phosphoric acid solution for 1-10 hours, the phosphoric acid solution of the highland barley straw powder is filtered to obtain a solid phase, and the solid phase is dried at 80-120° C. for 6-16 hours to obtain highland barley straw powder pretreated with phosphoric acid.
[0020] Step S4, activating and carbonizing the highland barley straw powder pretreated with phosphoric acid in sequence to obtain a hard carbon material based on highland barley straw; During the activation process, the heating rate is 1-10°C / min, the activation temperature is 350-650°C, and the activation time is 1-10h; during the carbonization process, the heating rate is 1-10°C / min, the carbonization temperature is 1000-1600°C, and the carbonization time is 1-10h.
[0021] In this embodiment, highland barley straw powder is immersed in phosphoric acid solution and activated at low temperature. On the one hand, phosphoric acid solution has good wettability to straw, and phosphoric acid molecules gradually penetrate into the interior of straw under the swelling effect of protonic acid, promoting the hydrolysis of cellulose in straw; on the other hand, during the low-temperature activation process, phosphoric acid can promote the dehydration of precursor and promote the aromatization of carbon atoms and the fusion of aromatic rings, thereby improving the carbon yield; at the same time, phosphoric acid and hydroxyl groups in the precursor undergo cross-linking condensation reaction to form phosphate ester bonds, which are destroyed at a certain temperature and leave pores after washing; in addition, phosphoric acid liquid impregnation modification has the characteristics of simplicity and high efficiency. Then, the microporous structure obtained by low-temperature activation of phosphoric acid is shrunk into closed pores by high-temperature carbonization, and the orderly growth of carbon layer is inhibited by cross-linking reaction between phosphoric acid and oxygen-containing groups, and finally a hard carbon material with both graphite-like microcrystals and closed-pore structure is prepared.
[0022] The second embodiment of the present invention provides a method for preparing a hard carbon material based on highland barley straw, which is obtained by using the above-mentioned method for preparing a hard carbon material based on highland barley straw.
[0023] The third embodiment of the present invention provides an application of hard carbon material prepared based on highland barley straw in the negative electrode of a sodium ion battery.
[0024] Specifically, the prepared hard carbon material is used as the negative electrode material of the sodium ion battery, mixed with conductive carbon black and sodium carboxymethyl cellulose to form a pole piece, a metal sodium sheet is used as the counter electrode, glass fiber paper is used as the separator, and an ether electrolyte is selected as the electrolyte to be assembled into a button battery.
[0025] Example 1 Step S1, peeling, crushing, washing, treating with hydrochloric acid solution, filtering and drying highland barley straw in sequence to obtain highland barley straw powder with low ash content; Step S2, placing the highland barley straw powder in a muffle furnace, heating it to 250° C. at a rate of 5° C. / min, and keeping it warm for 3 hours to obtain pre-oxidized highland barley straw powder; Step S3, immersing the pre-oxidized highland barley straw powder in a phosphoric acid solution for 5 hours at a mass ratio of 1:1.5, and filtering and drying to obtain phosphoric acid pretreated highland barley straw powder; Step S4, placing the highland barley straw powder pretreated with phosphoric acid in a tubular furnace protected by an inert atmosphere, heating it to 500°C at a rate of 5°C / min, keeping it warm for 3 hours, and performing low-temperature activation; then continuing to heat it to 1300°C at a rate of 5°C / min, keeping it warm for 3 hours, and obtaining a hard carbon material based on highland barley straw after cooling.
[0026] The hard carbon material obtained in this example was subjected to SEM and XRD tests, and the results are as follows: Figure 1 and Figure 2 As shown, from Figure 1It can be seen that the surface of the prepared hard carbon material is relatively smooth and still maintains the hollow tubular fiber structure of straw. This unique structure is conducive to the diffusion and transmission of sodium ions and electrolyte solutions, while providing more active sites for sodium storage. Figure 2 It can be seen that the prepared hard carbon material does not show obvious crystal diffraction peaks. Only two broadened diffraction peaks are observed at positions near 22~24º and 43º, which correspond to the (002) and (100) peaks of graphite materials, confirming the amorphous structural characteristics of hard carbon.
[0027] The prepared hard carbon material was used as the negative electrode material of sodium ion battery, mixed with conductive carbon black and sodium carboxymethyl cellulose to make a pole piece, with a metal sodium sheet as the counter electrode, glass fiber paper as the separator, and an ether electrolyte as the electrolyte, assembled into a button battery to measure its electrochemical performance. Figure 3-5 As shown. Figure 3 It can be seen that the reversible specific capacity of the hard carbon material at a current density of 20 mA / g is 315 mAh / g, and the first coulombic efficiency is 79.1%. Figure 4 It can be seen that at a current density of 100 mA / g, the reversible capacity of 275 mAh / g can still be maintained after 100 cycles, showing excellent cycle stability. Figure 5 It can be seen that the battery still has a high capacity of 150 mAh / g at a large current density of 1A / g, and it can be seen that the material has excellent rate performance.
[0028] Example 2 Step S1, peeling, crushing, washing, treating with sulfuric acid solution, filtering and drying highland barley straw in sequence to obtain low-ash highland barley straw powder; Step S2, placing the highland barley straw powder in a muffle furnace, heating it to 200° C. at a rate of 5° C. / min, and keeping it warm for 5 hours to obtain pre-oxidized highland barley straw powder; Step S3, immersing the pre-oxidized highland barley straw powder in a phosphoric acid solution for 6 hours at a mass ratio of 1:1, and filtering and drying to obtain phosphoric acid pretreated highland barley straw powder; Step S4, placing the highland barley straw powder pretreated with phosphoric acid in a tubular furnace protected by an inert atmosphere, heating it to 500°C at a rate of 5°C / min, keeping it warm for 3 hours, and performing low-temperature activation; then continuing to heat it to 1300°C at a rate of 5°C / min, keeping it warm for 3 hours, and obtaining a hard carbon material based on highland barley straw after cooling.
[0029] Example 3 Step S1, peeling, crushing, washing, treating with hydrofluoric acid solution, filtering and drying highland barley straw in sequence to obtain highland barley straw powder with low ash content; Step S2, placing the highland barley straw powder in a muffle furnace, heating it to 100° C. at a rate of 5° C. / min, and keeping it warm for 7 hours to obtain pre-oxidized highland barley straw powder; Step S3, immersing the pre-oxidized highland barley straw powder in a phosphoric acid solution at a mass ratio of 1:1 for 8 hours, filtering and drying to obtain phosphoric acid pretreated highland barley straw powder; Step S4, placing the highland barley straw powder pretreated with phosphoric acid in a tubular furnace protected by an inert atmosphere, heating it to 600°C at a rate of 5°C / min, keeping it warm for 3 hours, and performing low-temperature activation; then continuing to heat it to 1200°C at a rate of 5°C / min, keeping it warm for 3 hours, and obtaining a hard carbon material based on highland barley straw after cooling.
[0030] Example 4 Step S1, peeling, crushing, washing, treating with sulfuric acid solution, filtering and drying highland barley straw in sequence to obtain low-ash highland barley straw powder; Step S2, placing the highland barley straw powder in a muffle furnace, heating it to 250° C. at a rate of 5° C. / min, and keeping it warm for 5 hours to obtain pre-oxidized highland barley straw powder; Step S3, immersing the pre-oxidized highland barley straw powder in a phosphoric acid solution for 5 hours at a mass ratio of 1:2, and filtering and drying to obtain phosphoric acid pretreated highland barley straw powder; Step S4, placing the highland barley straw powder pretreated with phosphoric acid in a tubular furnace protected by an inert atmosphere, heating it to 600°C at a rate of 5°C / min, keeping it warm for 3 hours, and performing low-temperature activation; then continuing to heat it to 1400°C at a rate of 7°C / min, keeping it warm for 3 hours, and obtaining a hard carbon material based on highland barley straw after cooling.
[0031] Example 5 Step S1, peeling, crushing, washing, treating with hydrochloric acid solution, filtering and drying highland barley straw in sequence to obtain highland barley straw powder with low ash content; Step S2, placing the highland barley straw powder in a muffle furnace, heating it to 300° C. at a rate of 5° C. / min, and keeping it warm for 2 hours to obtain pre-oxidized highland barley straw powder; Step S3, immersing the pre-oxidized highland barley straw powder in a phosphoric acid solution for 5 hours at a mass ratio of 1:1.6, and filtering and drying to obtain phosphoric acid pretreated highland barley straw powder; Step S4, placing the highland barley straw powder pretreated with phosphoric acid in a tubular furnace protected by an inert atmosphere, heating it to 600°C at a rate of 3°C / min, keeping it warm for 2 hours, and performing low-temperature activation; then continuing to heat it to 1300°C at a rate of 4°C / min, keeping it warm for 3 hours, and obtaining a hard carbon material based on highland barley straw after cooling.
[0032] Example 6 Step S1, peeling, crushing, washing, treating with hydrochloric acid solution, filtering and drying highland barley straw in sequence to obtain highland barley straw powder with low ash content; Step S2, placing the highland barley straw powder in a muffle furnace, heating it to 250° C. at a rate of 3° C. / min, and keeping it warm for 2 hours to obtain pre-oxidized highland barley straw powder; Step S3, immersing the pre-oxidized highland barley straw powder in a phosphoric acid solution at a mass ratio of 1:1 for 10 hours, filtering and drying to obtain highland barley straw powder pretreated with phosphoric acid; Step S4, placing the highland barley straw powder pretreated with phosphoric acid in a tubular furnace protected by an inert atmosphere, heating it to 500°C at a rate of 3°C / min, keeping it warm for 3 hours, and performing low-temperature activation; then continuing to heat it to 1300°C at a rate of 1°C / min, keeping it warm for 3 hours, and obtaining a hard carbon material based on highland barley straw after cooling.
[0033] Comparative Example Step S1, peeling, crushing, washing, treating with hydrochloric acid solution, filtering and drying highland barley straw in sequence to obtain highland barley straw powder with low ash content; Step S2, placing the highland barley straw powder in a muffle furnace, heating it to 250° C. at a rate of 3° C. / min, and keeping it warm for 2 hours to obtain pre-oxidized highland barley straw powder; Step S3, placing the pre-oxidized highland barley straw powder in a tubular furnace protected by an inert atmosphere, heating it to 500°C at a rate of 3°C / min, keeping it warm for 3 hours, and performing low-temperature activation; then continuing to heat it to 1300°C at a rate of 1°C / min, keeping it warm for 3 hours, and obtaining a hard carbon material based on highland barley straw after cooling.
[0034] The electrical properties of the hard carbon material obtained in the comparative example were tested, and the reversible specific capacity of the hard carbon material was only 267 mAh / g, and the first coulombic efficiency was only 70%.
[0035] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A method for preparing hard carbon material based on highland barley straw, characterized in that: include: preparing highland barley straw powder; Pre-oxidizing the highland barley straw powder to obtain pre-oxidized highland barley straw powder, wherein the pre-oxidation temperature is 150-300° C. and the insulation time is 1-10 hours; The pre-oxidized highland barley straw powder is immersed in a phosphoric acid solution to prepare a phosphoric acid pretreated highland barley straw powder; The highland barley straw powder pretreated with phosphoric acid is activated and carbonized in sequence to obtain a hard carbon material based on highland barley straw; In the activation process, the activation temperature is 350-650°C and the activation time is 1-10h; in the carbonization process, the carbonization temperature is 1000-1600°C and the carbonization time is 1-10h.
2. The method for preparing hard carbon material based on highland barley straw according to claim 1, characterized in that: The mass ratio of the pre-oxidized highland barley straw powder to the phosphoric acid solution is 1:0.1-8, and the immersion time is 1-10 hours.
3. The method for preparing hard carbon material based on highland barley straw according to claim 1, characterized in that: The highland barley straw powder pretreated with phosphoric acid is obtained by the following method: filtering and drying the phosphoric acid solution of highland barley straw powder obtained by soaking; Among them, the drying temperature is 80-120℃, and the drying time is 6-16 h.
4. The method for preparing hard carbon material based on highland barley straw according to claim 1, characterized in that: The heating rates of the pre-oxidation process, activation process and carbonization process are all 1-10°C / min.
5. The method for preparing hard carbon material based on highland barley straw according to claim 1, characterized in that: The highland barley straw powder is obtained by the following method: The highland barley straw is peeled, crushed, washed, acid-treated, filtered and dried in sequence.
6. The method for preparing hard carbon material based on highland barley straw according to claim 1, characterized in that: The solution used for the acid treatment is hydrochloric acid solution, sulfuric acid solution, nitric acid solution or hydrofluoric acid solution.
7. A method for preparing a hard carbon material based on highland barley straw, characterized in that: The hard carbon material is obtained by using the method for preparing hard carbon material based on highland barley straw as described in any one of claims 1 to 6.
8. Use of the hard carbon material prepared based on highland barley straw as claimed in claim 7 in the negative electrode of a sodium ion battery.